2008
DOI: 10.1093/nar/gkn459
|View full text |Cite
|
Sign up to set email alerts
|

Assembling of G-strands into novel tetra-molecular parallel G4-DNA nanostructures using avidin-biotin recognition

Abstract: We describe a method for the preparation of novel long (hundreds of nanometers), uniform, inter-molecular G4-DNA molecules composed of four parallel G-strands. The only long continuous G4-DNA reported so far are intra-molecular structures made of a single G-strand. To enable a tetra-molecular assembly of the G-strands we developed a novel approach based on avidin–biotin biological recognition. The steps of the G4-DNA production include: (i) Enzymatic synthesis of long poly(dG)-poly(dC) molecules with biotinyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 45 publications
1
72
0
Order By: Relevance
“…[6] When using the same number of tetrads for the construction of the tetra-molecular G4-DNA and the 2 intra-molecular G4-DNA, the former are thicker and shorter than the latter molecules. [5] This suggests that the folding orientation of the strands, which form the backbone, affects the molecular structure, i.e. the tetrad unit and the tetrad-tetrad stacking.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[6] When using the same number of tetrads for the construction of the tetra-molecular G4-DNA and the 2 intra-molecular G4-DNA, the former are thicker and shorter than the latter molecules. [5] This suggests that the folding orientation of the strands, which form the backbone, affects the molecular structure, i.e. the tetrad unit and the tetrad-tetrad stacking.…”
mentioning
confidence: 99%
“…This type of intra-molecular G4-DNA possessed distinct polarizability, in contrast to native dsDNA, which gave no discernible signal. [4] That study was followed by the synthesis and EFM measurements of tetra-molecular G4-DNA [5] (Figure 1b, right), which is stable in the absence of metal cations, and was shown to possess a clear signal of polarizability as well.For intra-molecular and tetra-molecular G4-DNA that are composed of the same number of tetrads, AFM imaging [5] showed that tetra-molecular G4-DNA, adsorbed on a mica surface, resembles a tadpole with a large avidin "head" and a straight elongated "tail" (Figure 1c), while intra-molecular G4-DNA appears longer and thinner and is more flexible on the surface, forming curved lines. In this study, we synthesized two pairs of corresponding lengths of tetramolecular G4-DNA and intra-molecular G4-DNA (see Figure 1c and Figure S1).…”
mentioning
confidence: 99%
See 3 more Smart Citations